A study on TQM practices and employees' job satisfaction: case study of Sarawak Energy Berhad, Kuching / Justin John Mari & Raden Mohd Azlan Raden Perhan - Mari, Justin John; Raden Perhan, Raden Mohd Azlan (2012)
Total Quality Management practices have brought many private and public sector into success. This new management principle is a key for maintaining competitive advantages and helps the organizations to improve its overall effectiveness and performance through continuous improvement efforts. The study examines the TQM practices on job satisfaction among the employees. The TQM practices such as customer focus; teamwork; organizational trust; organizational culture and reward and recognition are among the elements that have impact on job satisfaction directly. A random sample of 150 employees of Sarawak Energy Berhad (SEB), Kuching, Sarawak have been selected and required to answer the survey regarding this TQM practices. The employees’ level of job satisfaction and their perception on TQM practices were examined. Apparently, most of the employees having high and positive level of job satisfaction and agreed that TQM’s elements were regularly practices in the organization. The employees approved that customer focus and organizational trust is eminent elements of TQM practices which having strong relationship with their job satisfaction. The study also shows that reward and recognition as well as organizational culture less associated with their level of job satisfaction in practicing TQM in the organization. The implementation and practicing of TQM must be well-communicated to the employees to assure no resistance to change for work improvement while maintaining their satisfaction over their jobs regularly.